An ultra-thin lead alloy base plate for lead-acid batteries and a preparation process and application thereof

CN120961627BActive Publication Date: 2026-10-27JIESHOU HUAYU POWER SUPPLY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511322481.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-16
Publication Date
2026-10-27
Estimated Expiration
2045-09-16

AI Technical Summary

Technical Problem

例如,专利CN103181019B公开的汽车用电池极板连续轧制工艺,通过7-10道次轧制将初始厚度8-11mm的铅铸坯减薄至0.8-1.2mm,虽实现了一定程度的减薄,但最终厚度仍高于0.6mm,且未针对超薄带材的轧制稳定性进行优化;专利CN106025383A提出的阀控式铅酸蓄电池连铸连轧工艺,将铅带基板厚度控制在0.6-2.5mm,其核心改进点在于板栅筋条的多边形整形设计,而非基板厚度的突破性减薄;专利CN102005574A虽通过粉末轧制工艺将基板厚度降至0.2mm,但该技术依赖铅粉与添加剂的混合压制,生产流程复杂、成本较高,且粉末冶金结合强度难以满足高功率放电场景的力学要求,无法替代主流的连铸连轧工艺

Benefits of technology

(1)本发明采用9道分段轧制策略(粗轧15%~20%、中轧10%~15%、精轧5%~8%),减薄铅带基板厚度,相同面积下降低铅材用量,在连铸连轧工艺中实现超薄基板的工业化生产。应用于铅酸蓄电池板栅上使得电池结构更紧凑,相同容量下,超薄基板可减少极板厚度,使电池整体体积更小、重量更轻;反之,相同体积下可增加极板数量,提升电池容量。分段轧制细化了铅带晶粒组织,使基板的抗拉强度、延展性更优,延长电池使用寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120961627B_ABST
    Figure CN120961627B_ABST
Patent Text Reader

Abstract

The application discloses a kind of lead-acid battery ultra-thin lead alloy base plate and its preparation process and application, belong to lead-acid battery preparation technical field.The process adopts 9 subsection rolling strategy: rough rolling stage (1~3 pass, reduction 15%~20%) eliminates casting organization defect, middle rolling stage (4~6 pass, 10%~15%) stabilizes material flow, and thickness precision is controlled in finishing rolling stage (7~9 pass, 5%~8%);While being combined with roll hard chromium plating, hydraulic AGC dynamic adjustment, 100~150 DEG C warm rolling, water-based lubricant, finishing rolling air cooling and power winding device, it can also be adapted to 10 pass and above pass to prepare thinner base plate.The base plate prepared by the process is 0.25~0.3mm in thickness, with a tolerance of ≤±0.009mm, a tensile strength of ≥17.5MPa, and a winding wrinkle rate of ≤0.5%;When applied to grid, the battery 5C capacity retention rate is ≥88.3%, and has wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lead-acid battery manufacturing technology, specifically relating to an ultra-thin lead alloy substrate for lead-acid batteries, its manufacturing process, and its application. Background Technology

[0002] With the increasing demands for cost-effectiveness in energy storage equipment from the new energy industry, and the direct impact of raw material price fluctuations on lead-acid battery production costs, the industry urgently needs to achieve a synergistic breakthrough in "cost reduction and efficiency improvement" and "performance upgrade" through process optimization. Among these technologies, continuous casting and rolling grid forming has gradually replaced traditional gravity casting and pressure casting processes, becoming the mainstream technology for lead-acid battery grid preparation due to its high production efficiency, uniform substrate structure, and good grid forming precision.

[0003] In the manufacturing cost structure of lead-acid batteries, lead material accounts for as much as 60%-70%, and the thickness of the lead strip substrate, as the core substrate of the grid, directly determines the amount of lead material used per unit battery. Under the existing continuous casting and rolling stamping process system, the thickness of the lead strip substrate is generally maintained at ≥0.6mm due to limitations in the precision of rolling equipment, the plasticity of lead alloy materials, and the level of process control. For example, the continuous rolling process for automotive battery plates disclosed in patent CN103181019B reduces the initial thickness of lead casting billets from 8-11mm to 0.8-1.2mm through 7-10 rolling passes. Although it achieves a certain degree of thinning, the final thickness is still higher than 0.6mm, and it does not optimize the rolling stability of ultra-thin strips. The valve-regulated lead-acid battery continuous casting and rolling process proposed in patent CN106025383A controls the thickness of the lead strip substrate to 0.6-2.5mm. Its core improvement lies in the polygonal shaping design of the grid ribs, rather than a breakthrough reduction in substrate thickness. Although patent CN102005574A reduces the substrate thickness to 0.2mm through powder rolling, this technology relies on the mixing and pressing of lead powder and additives, resulting in a complex production process and high cost. Furthermore, the bonding strength of powder metallurgy is difficult to meet the mechanical requirements of high-power discharge scenarios, and it cannot replace the mainstream continuous casting and rolling process.

[0004] Currently, existing technologies have two major limitations: First, the substrate thickness of ≥0.6mm leads to high lead consumption, which restricts further reduction in battery costs. Second, the thicker substrate limits the flexibility of battery structure design. For example, in scenarios with specific requirements for high-current discharge performance, such as automotive start-stop batteries and high-rate energy storage batteries, if the thickness of the negative substrate can be further reduced, more electrode plates can be designed in the same battery casing. However, existing processes cannot achieve a precise processing scheme for the stable preparation of ultra-thin substrates, which leads to problems such as wrinkles, breakage, and excessive thickness deviation in ultra-thin strips during rolling, making it difficult to meet the needs of industrial production. Summary of the Invention

[0005] One of the objectives of this invention is to provide a manufacturing process for an ultra-thin lead alloy substrate for lead-acid batteries, further reducing the thickness of the lead strip substrate for lead-acid batteries, while providing more optimization possibilities for battery design (such as improving the high current discharge requirements in specific scenarios by using multiple electrode plate ratios), and achieving more precise processing control of the ultra-thin lead strip.

[0006] The second objective of this invention is to provide an ultra-thin lead alloy substrate for lead-acid batteries, which is prepared using the aforementioned preparation process for ultra-thin lead alloy substrates for lead-acid batteries.

[0007] The third objective of this invention is to provide an application of an ultra-thin lead alloy substrate for lead-acid batteries in lead-acid battery grids, wherein the ultra-thin lead alloy substrate for lead-acid batteries used is the aforementioned ultra-thin lead alloy substrate for lead-acid batteries.

[0008] The objective of this invention can be achieved through the following technical solutions: A process for fabricating an ultrathin lead alloy substrate for lead-acid batteries, employing a segmented rolling strategy, includes the following steps: S1, Rough rolling stage: Passes 1-3, reduction rate 15%-20%; S2, intermediate rolling stage: passes 4 to 6, reduction rate 10% to 15%; S3, Finishing rolling stage: Passes 7-9, reduction rate 5%-8%; During the segmented rolling process, the surface of the rolls is treated with hard chrome plating, and the roll gap is dynamically adjusted in combination with a hydraulic automatic thickness control system. The rolling process uses a water-based lubricant and adds an air-cooling device in the finishing rolling stage to reduce the temperature of the lead strip; After the finishing rolling stage, a power conveying device is added to the winding stage. The winding tension and speed are controlled by active power to make the winding process smooth and obtain the lead alloy substrate.

[0009] Furthermore, the rolling temperature is controlled at 100~150℃, the rolling speed for the first to third passes is 10~15m / min, the rolling speed for the fourth to sixth passes is 15~20m / min, and the rolling speed for the seventh to ninth passes is 20~30m / min.

[0010] Furthermore, the roll is either a flat roll or a slightly convex roll.

[0011] Furthermore, the thickness of the hard chrome plating on the surface of the roll is 5~10μm.

[0012] Furthermore, the Vickers hardness of the hard chrome plating on the surface of the roll is ≥800HV.

[0013] Furthermore, the hydraulic automatic thickness control system is used to ensure that the lead strip extends uniformly along the width direction.

[0014] Furthermore, the water-based lubricant is prepared by mixing Jasper-RLF901 emulsified cutting fluid and water at a volume ratio of 1:(180-220).

[0015] Furthermore, the temperature of the lead strip is reduced to ≤40°C.

[0016] Furthermore, the active power control stabilizes the winding tension at 50N±2N.

[0017] Furthermore, the number of rolling passes can be ≥10. When the number of rolling passes is ≥10, the segmented rolling strategy is adjusted as follows: the roughing stage consists of passes 1 to 4 with a reduction rate of 12% to 18%; the intermediate rolling stage consists of passes 5 to 8 with a reduction rate of 8% to 13%; and the finishing rolling stage consists of pass 9 and subsequent passes with a reduction rate of 4% to 7%. The rolling temperature, rolling speed, roll control, and coiling control of each stage are adapted to the process parameters of the corresponding stage when rolling 9 passes.

[0018] An ultra-thin lead alloy substrate for lead-acid batteries is prepared by the aforementioned process for preparing ultra-thin lead alloy substrates for lead-acid batteries.

[0019] The application of an ultra-thin lead alloy substrate for lead-acid batteries in lead-acid battery grids, wherein the ultra-thin lead alloy substrate for lead-acid batteries is the aforementioned ultra-thin lead alloy substrate for lead-acid batteries.

[0020] The beneficial effects of this invention are: (1) This invention employs a 9-stage segmented rolling strategy (rough rolling 15%~20%, intermediate rolling 10%~15%, and finish rolling 5%~8%) to reduce the thickness of the lead strip substrate, thereby reducing the amount of lead material used for the same area and achieving industrial production of ultra-thin substrates in a continuous casting and rolling process. When applied to lead-acid battery grids, this results in a more compact battery structure. For the same capacity, the ultra-thin substrate can reduce the thickness of the electrode plates, making the overall battery smaller and lighter; conversely, for the same volume, the number of electrode plates can be increased, thus increasing battery capacity. Segmented rolling refines the grain structure of the lead strip, resulting in better tensile strength and ductility of the substrate, and extending battery life.

[0021] (2) This invention employs a hydraulic automatic thickness control system (hydraulic AGC) for dynamic roll gap adjustment and a hard chrome-plated roll design, combined with reduction rate control during the finishing rolling stage, to reduce lead strip thickness tolerance and improve surface finish. This solves the problems of uneven thickness, edge defects, and lead sticking to rolls that are prone to occur in existing ultra-thin strip rolling. At the same time, the 100~150℃ warm rolling range and multi-pass deformation heat distribution mechanism avoid grain coarsening caused by local overheating of lead material, ensuring the compactness of the substrate structure and the improvement of mechanical properties.

[0022] (3) The present invention uses a combination of water-based lubricant and a fine rolling air-cooling device to reduce the amount of lubricant residue on the lead strip surface, control the final rolling temperature, and reduce the cost of subsequent cleaning processes; the newly added power conveying winding device solves the wrinkling and deformation problems that occur in the existing non-powered winding re-production, realizes continuous and stable winding, and improves production efficiency. Attached Figure Description

[0023] The invention will now be further described with reference to the accompanying drawings.

[0024] Figure 1 This is a schematic diagram of the preparation process in Example 1 of the present invention; Figure 2 This is a schematic diagram of the preparation process of Comparative Example 1 of the present invention. Detailed Implementation

[0025] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below.

[0026] This invention provides a process for preparing an ultrathin lead alloy substrate for lead-acid batteries, comprising the following steps: 1. Optimization of run allocation and reduction rate Segmented rolling strategy: Rough rolling stage (first 3 passes): Rapidly thin the material with a large reduction rate (15%~20%) to eliminate casting defects.

[0027] Intermediate rolling stage (passes 4-6): medium reduction rate (10%-15%), gradually adjust the thickness and stabilize the material flow.

[0028] Finishing rolling stage (passes 7-9): small reduction rate (5%-8%), with a focus on controlling thickness tolerance and surface quality.

[0029] Cumulative deformation distribution: The total reduction remains unchanged, but it is distributed across more passes. The original total reduction rate of 80% for 7 passes is gradually achieved by changing it to 9 passes.

[0030] 2. Roll pass and roll gap design

[0031] Pass shape optimization: Flat rolls or slightly convex rolls are used. Flat rolls are suitable for narrow lead strips and can ensure the flatness of the strip. Slightly convex rolls are for wide lead strips and can compensate for the "edge thinning" phenomenon during rolling, so that the thickness difference across the entire width is ≤0.005mm, which can meet the preparation requirements of different specifications of battery grids. Combined with dynamic roll gap adjustment technology (hydraulic AGC), the lead strip is ensured to be uniformly extended in each pass.

[0032] Roll surface treatment: Adding a hard chrome plating layer to the roll surface reduces lead adhesion and extends roll life. When the plating thickness is <5μm, the wear resistance is insufficient, and it is easily scratched by lead, leading to surface defects in the strip. When the thickness is >10μm, the adhesion between the plating layer and the roll substrate decreases, making it easy to detach and contaminate the lead strip. Limiting the Vickers hardness of the roll substrate can improve surface wear resistance, effectively preventing lead atoms from diffusing to the roll surface, reducing strip scratches caused by lead adhesion at the source, and reducing the frequency of roll regrinding, thus saving maintenance costs.

[0033] 3. Temperature control and process parameters

[0034] Warm rolling process: Lead has a low melting point (327℃), so the rolling temperature needs to be controlled in the range of 100~150℃. If the temperature is below 100℃, the plasticity is insufficient and it is easy to cause rolling cracks. If the temperature is above 150℃, the deformation heat will be concentrated and cause local overheating. By distributing the deformation heat through multiple passes, local overheating can be avoided and grain coarsening can be prevented.

[0035] Rolling speed matching: rough rolling at 10~15m / min can ensure that the casting structure is fully broken (eliminating defects such as porosity and segregation), intermediate rolling at 15~20m / min achieves a smooth transition, and finishing rolling at 20~30m / min improves production efficiency while ensuring thickness accuracy. This is a significant improvement in efficiency compared to the existing single-speed (15~20m / min) process.

[0036] 4. Lubrication and Cooling System

[0037] Lubricant Selection: Use a water-based lubricant (Jasper-RLF901 emulsified cutting fluid, mixed with water at a ratio of 1:(180-220)) to reduce residue on the lead strip surface. If the concentration is too high, the lubricant residue will be excessive, requiring multiple cleaning steps; if the concentration is too low (e.g., 1:300), the lubrication effect will be insufficient, easily leading to wrinkling of the strip surface. A 1:180-220 ratio requires no additional cleaning, and the rust-inhibiting components of Jasper-RLF901 can prevent oxidation and rust on the lead strip within 72 hours of storage.

[0038] Segmented cooling: An air-cooling device is added during the finishing rolling stage to control the final rolling temperature to ≤40℃. If the final rolling temperature is >40℃, the lead strip is prone to plastic deformation due to residual heat during winding, requiring a subsequent leveling process. By reducing the temperature to ≤40℃ through the air-cooling device, the straightness of the lead strip after winding is ≤1mm / m, eliminating the need for the leveling step, while also avoiding surface oxidation caused by high temperature and improving the conductivity of the substrate.

[0039] 5. Optimized winding design: The existing design lacks a powered conveyor during the winding stage, relying on a downstream roller to drive the winding. When the lead strip thickness reaches below 0.4mm, the lead strip is severely deformed during winding, which cannot meet normal production requirements. The new design adds a powered conveyor, which stabilizes the tension at 50N±2N, ensuring smooth winding and meeting normal production needs.

[0040] In some embodiments, the rolling passes can be ≥10. When the rolling passes are ≥10, the segmented rolling strategy is adjusted as follows: the roughing stage consists of passes 1 to 4 with a reduction rate of 12% to 18%; the intermediate rolling stage consists of passes 5 to 8 with a reduction rate of 8% to 13%; and the finishing rolling stage consists of pass 9 and subsequent passes with a reduction rate of 4% to 7%. The rolling temperature, rolling speed, roll control, and coiling control of each stage are adapted to the process parameters of the corresponding stage when rolling 9 passes.

[0041] When fabricating thinner substrates, increasing the number of roughing passes and reducing the single-pass reduction rate (from 15%~20% to 12%~18%) allows for a more uniform distribution of deformation per pass, making it easier to control accumulated deformation heat and avoiding the risk of cracking. Simultaneously, reducing the finishing rolling reduction rate to 4%~7% further improves thickness accuracy and expands the process's adaptability to substrates of different thicknesses.

[0042] The specific embodiments of the present invention will be described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments.

[0043] Example 1

[0044] This embodiment provides an ultra-thin lead alloy substrate for lead-acid batteries, which is prepared through the following steps: I. Raw material pretreatment Continuous casting billet forming: molten lead alloy (temperature 350℃) is cast into a billet with a thickness of 5.0mm, a width of 200mm, and a length of 50m using a horizontal continuous casting machine. The cooling rate of the billet is controlled at 15℃ / s to avoid coarse grains. Surface treatment of billet: Grind the oxide layer on the surface of the billet with 120-grit sandpaper until the metallic luster is exposed, then spray and clean with anhydrous ethanol, and after drying, the surface roughness Ra≤2.0μm.

[0045] II. Pre-rolling equipment

[0046] Coating treatment: The process of electroplating hard chrome is adopted, with a coating thickness of 8μm and a Vickers hardness of 850HV. Lubricant preparation: Jasper-RLF901 emulsified cutting fluid and deionized water are mixed at a volume ratio of 1:200; III. Specific Operations of 9-Stage Rolling (a) Rough rolling stage (passes 1-3, to eliminate casting defects) Pass 1: The pretreated billet is fed into the rolling mill with an inlet temperature of 25°C, a reduction rate of 18%, a roll gap of 4.1 mm, a roll temperature of 120°C, and a speed of 12 m / min. Second pass: 17% reduction, 3.47mm roll gap, 125℃ roll temperature, 12m / min speed; Third pass: 16% reduction, 2.91mm roll gap, 130℃ roll temperature, 12m / min speed; (ii) Intermediate rolling stage (passes 4-6, stabilizing thickness and flow) 4th pass: 13% reduction, 2.52mm roll gap, 130℃ roll temperature, 16m / min speed, lubricant spraying turned on; 5th pass: 12% reduction, 2.20mm roll gap, 128℃ roll temperature, 16m / min speed; 6th pass: 11% reduction, 1.94mm roll gap, 125℃ roll temperature, 16m / min speed; (III) Finish rolling stage (passes 7-9, controlling accuracy and surface finish) 7th pass: 7% reduction, 1.79mm roll gap, 120℃ roll temperature, 25m / min speed, air cooling on; 8th pass: 6% reduction, 1.67mm roll gap, 118℃ roll temperature, 25m / min speed; 9th pass: 5% reduction, 1.58mm roll gap, 115℃ roll temperature, 25m / min speed; IV. Collection Rewinding operation: The lead strip enters the power rewinding device, the tension is stabilized at 50N±2N, the rewinding diameter increases from Φ100mm to Φ500mm, and the lead strip is wrinkle-free and deviates after rewinding.

[0047] The above steps are as follows Figure 1 As shown.

[0048] V. Application

[0049] The lead strip is punched into a grid (grid ribs 1.2mm×1.0mm, hole diameter 6mm×8mm), coated with lead paste, and then fitted with a 12V / 60Ah lead-acid battery.

[0050] Example 2

[0051] The difference between this embodiment and Embodiment 1 is that the number of passes is allocated as follows: roughing 1 to 3 passes (20%, 19%, 18%), intermediate rolling 4 to 6 passes (15%, 14%, 13%), and finishing rolling 7 to 9 passes (8%, 7%, 6%). The remaining raw materials and preparation process are the same as in Example 1.

[0052] Example 3

[0053] The difference between this embodiment and Embodiment 1 is that the rolls used are micro-convex rolls (convexity 0.02mm). The remaining raw materials and preparation process are the same as in Example 1.

[0054] Example 4

[0055] The difference between this embodiment and Embodiment 1 is that the volume ratio of Jasper-RLF901 to water is 1:180. The remaining raw materials and preparation process are the same as in Example 1.

[0056] Example 5

[0057] The difference between this embodiment and Embodiment 1 is that the pass allocation is as follows: roughing 1-4 passes (15%, 14%, 13%, 12%), intermediate rolling 5-8 passes (10%, 9%, 8%, 7%), and finishing rolling 9-10 passes (6%, 5%); the target thickness of the lead alloy substrate is 0.25 mm. The remaining raw materials and preparation process are the same as in Example 1.

[0058] Comparative Example 1

[0059] The difference between this comparative example and Example 1 is that it uses a 7-pass conventional rolling process, with the steps as follows: Figure 2 As shown; Pass allocation: 7 passes (reduction rate 25%, 20%, 15%, 10%, 8%, 6%, 5%). Rolls: Uncoated flat rolls; Temperature: 150~180℃ (and without precise control); Rewinding: Non-powered rewinding; Other: No AGC, lubricant is machine oil (1:50); The remaining raw materials and preparation process are the same as in Example 1.

[0060] Comparative Example 2

[0061] The difference between this comparative example and Example 1 is that the rolls used have no hard chromium plating (substrate hardness 250HV). The remaining raw materials and preparation process are the same as in Example 1.

[0062] Comparative Example 3

[0063] The difference between this comparative example and Example 1 is that the roll gap in the 9-pass AGC-free system process is manually adjusted. The remaining raw materials and preparation process are the same as in Example 1.

[0064] Comparative Example 4

[0065] The difference between this comparative example and Example 1 is that the temperature in the 9-pass high-temperature rolling process is adjusted to 160~180℃; The remaining raw materials and preparation process are the same as in Example 1.

[0066] Performance testing

[0067] 1. Substrate thickness and tolerance: A laser thickness gauge (accuracy ±0.001mm) was used to measure 3 points every 100mm along the length of the strip, and the average value and maximum deviation were recorded; 2. Surface finish: Ra value (μm) was measured using a roughness tester; 3. Tensile strength: Tested using a universal testing machine in accordance with GB / T228.1-2021 "Metallic materials - Tensile testing - Part 1: Test at room temperature"; 4. Wrinkle rate: The percentage of wrinkled length on the surface of the strip after winding out of the total length; 5. High-current discharge performance of the battery: After the substrate is made into a grid, a 12V / 60Ah lead-acid battery is assembled, and the capacity retention rate at 5C rate (relative to 2C rate) is tested.

[0068] The results are shown in Table 1: Table 1

[0069] As can be seen from Table 1, the substrate thickness of Examples 1-5 is controlled at 0.25~0.3mm, which is significantly thinner than the 0.72mm of Comparative Example 1. Among them, Example 5 further reduced the thickness to 0.25mm through 10 optimizations, proving that the process can be adapted to the preparation requirements of thinner substrates and broaden the application scenarios.

[0070] The winding wrinkle rate of Examples 1-5 is only 0.2%~0.5%, far lower than the 12.5% ​​of Comparative Example 1, indicating that the newly added power conveying device effectively solved the problem of winding deformation of ultra-thin strips and met the requirements of continuous production. The reduction in thickness reduces the amount of lead material used in the same area, significantly reducing the cost of battery raw materials; at the same time, the 0.25~0.3mm ultra-thin substrate can achieve a smaller battery volume for the same capacity or an increase in the number of electrode plates for the same volume (for example, the 0.25mm substrate in Example 5 can hold 10% more electrode plates in the same shell than the 0.3mm substrate in Example 1), confirming the advantages of a more compact battery structure and increased capacity.

[0071] Compared with Comparative Example 2, Example 1 showed a significant reduction in surface Ra and winding wrinkle rate, indicating that the high hardness of the hard chrome plating effectively reduced surface scratches caused by lead sticking to the roller, solving the technical problem of "lead sticking to the roller" and improving surface smoothness.

[0072] The thickness tolerance of Example 1 was significantly improved compared to Comparative Example 3, while the tolerance of Example 3 was further reduced. This shows that the dynamic adjustment capability of the hydraulic AGC solved the problems of uneven extension in the width direction and thickness fluctuation, ensuring the dimensional consistency of the ultra-thin strip.

[0073] Compared to Comparative Example 4, Example 1 exhibits a significantly improved tensile strength. This is because the deformation heat in the 100-150℃ warm rolling range of this invention is distributed through multiple passes, avoiding the grain coarsening caused by high temperatures in Comparative Example 4. Example 3 (micro-convex roll) achieves a tensile strength of 19.5 MPa, further demonstrating that the synergy between roll design and warm rolling can optimize microstructure density and solve the problem of insufficient mechanical properties.

[0074] The 5C capacity retention rate of Example 1 was 88.5%, compared to only 65.2% in Comparative Example 1, and further increased to 91.3% in Example 5. This is because the ultra-thin substrate allows for the placement of more electrodes in the same casing, increasing the reaction area and shortening the ion diffusion path, thereby improving battery performance.

[0075] The above-disclosed embodiments are merely a few specific examples of the present invention. However, the embodiments of the present invention are not limited thereto, and any variations that can be conceived by those skilled in the art should fall within the protection scope of the present invention.

Claims

1. A process for preparing an ultrathin lead alloy substrate for lead-acid batteries, characterized in that, The nine-pass segmented rolling strategy includes the following steps: S1, Rough rolling stage: Passes 1-3, reduction rate 15%-20%; S2, intermediate rolling stage: passes 4 to 6, reduction rate 10% to 15%; S3, Finishing rolling stage: Passes 7-9, reduction rate 5%-8%; During the segmented rolling process, the surface of the rolls is treated with hard chrome plating. The thickness of the hard chrome plating on the roll surface is 5~10μm, and the Vickers hardness is ≥800HV. Combined with the hydraulic automatic thickness control system, the roll gap is dynamically adjusted to ensure that the lead strip is uniformly extended along the width direction. The rolling temperature is controlled at 100~150℃, the rolling speed for the first to third passes is 10~15m / min, the rolling speed for the fourth to sixth passes is 15~20m / min, and the rolling speed for the seventh to ninth passes is 20~30m / min; The rolling process uses a water-based lubricant, which is prepared by mixing Jasper-RLF901 emulsified cutting fluid and water at a volume ratio of 1:(180-220); and an air-cooling device is added in the finishing rolling stage to reduce the temperature of the lead strip to ≤40℃. After the finishing rolling stage, a power conveying device is added to the winding stage. The winding tension is stabilized at 50N±2N by active power control, so that the winding process is smooth and a lead alloy substrate with a thickness of 0.25~0.3mm is obtained.

2. The preparation process of the ultra-thin lead alloy substrate for lead-acid batteries according to claim 1, characterized in that, The roll is either a flat roll or a slightly convex roll.

3. The preparation process of the ultra-thin lead alloy substrate for lead-acid batteries according to claim 1, characterized in that, When the number of rolling passes is ≥10, the segmented rolling strategy is adjusted as follows: the roughing stage consists of passes 1 to 4 with a reduction rate of 12% to 18%; the intermediate rolling stage consists of passes 5 to 8 with a reduction rate of 8% to 13%; and the finishing rolling stage consists of pass 9 and subsequent passes with a reduction rate of 4% to 7%. The rolling temperature, rolling speed, roll control, and coiling control of each stage are adapted to the process parameters of the corresponding stage when rolling 9 passes.

4. An ultra-thin lead alloy substrate for lead-acid batteries, characterized in that, It is prepared by the preparation process of the ultra-thin lead alloy substrate for lead-acid batteries according to any one of claims 1-3.

5. The application of an ultra-thin lead alloy substrate for lead-acid batteries in lead-acid battery grids, characterized in that... The ultra-thin lead alloy substrate for lead-acid batteries used is the ultra-thin lead alloy substrate for lead-acid batteries as described in claim 4.

Citation Information

Patent Citations

  • Light plate grid for lead-acid storage battery and preparation method thereof

    CN102005574A

  • Automobile battery and electrode plate manufacturing method

    CN103181019B

  • Valve-control type lead acid storage battery and preparation method thereof

    CN106025383A

  • Manufacturing technology for net stamping plate grid for lead-acid storage battery

    CN105834213A

  • Advanced copper plate strip continuous rolling process

    CN119456669A